2022
DOI: 10.21203/rs.3.rs-1136749/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Correlation Between Long-Lasting Serum Lactate And Brain Mri Abnormality In Children With Status Epilepticus

Abstract: Background: Serum lactate was a biomarker implemented to estimate the prognosis in children suffered from status epilepticus (SE). Brain neuroimaging may demonstrate the site area, range of neuronal impairment and ischemic injury. This study aims to evaluate the correlation between long-lasting serum lactate with brain imaging abnormality reflected on Magnetic Resonance Imaging (MRI) in children suffered from SE. Method: This prospective analytical research was conducted from June-November 2018 in children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…27,28 Gunawan et al recently reported a correlation between serum lactate level and abnormal brain MRI findings in children with status epilepticus. 29 Lactate elevation and adenosine triphosphate depletion during the early phase of seizures are related to hypermetabolic neuronal damage. 29 Similarly, lactic acid was a strong associated factor of neuroimaging abnormalities in our pediatric patients experiencing their first afebrile seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Gunawan et al recently reported a correlation between serum lactate level and abnormal brain MRI findings in children with status epilepticus. 29 Lactate elevation and adenosine triphosphate depletion during the early phase of seizures are related to hypermetabolic neuronal damage. 29 Similarly, lactic acid was a strong associated factor of neuroimaging abnormalities in our pediatric patients experiencing their first afebrile seizure.…”
Section: Discussionmentioning
confidence: 99%
“…29 Lactate elevation and adenosine triphosphate depletion during the early phase of seizures are related to hypermetabolic neuronal damage. 29 Similarly, lactic acid was a strong associated factor of neuroimaging abnormalities in our pediatric patients experiencing their first afebrile seizure. In addition, Shapiro et al reported that unbound and free unconjugated bilirubin can selectively damage the central nervous system in the developing brain.…”
Section: Discussionmentioning
confidence: 99%